Faecal coliforms and pathogenic bacteria in borehole water and household storage in Ekalakala Ward, Machakos County, Kenya (African Journal of Science, Technology and Social Sciences, 2024)
The quality of drinking water is very vital to public health. Diarrhea can be caused by poor hygiene practices, inadequate sanitary action and unsafe drinking water. Globally, 1,000 children die annually due to controllable sanitation-related diarrhoea diseases.  Furthermore, Africa has been classified as the leading continent in cholera disease due to a lack of access to safe clean water and basic sanitation. Kenya is a water-scarce country in Africa leading to the drilling of many boreholes in the country. Almost all the households in Ekalakala ward, Machakos County used borehole water for various activities. This study aimed to determine faecal and pathogenic coliforms in borehole water at the source and households in Ekalakala ward, Machakos County. A mixed methods research design was adopted. The most probable number (MPN) technique was used to identify faecal coliforms (Escherichia. coli). Other pathogenic bacteria including Vibrio cholerae and Salmonella species were isolated using thiosulfate citrate bile salts and deoxycholate citrate agar respectively. MPN results showed that most of the samples were contaminated with faecal coliforms with a mean value of 171.3 MPN/100 ml of water. The proximity of boreholes to pit latrines was assessed using a checklist and confirmed that there was a moderate positive correlation of (r) = 0.45.  Borehole water in the Ekalakala ward was contaminated with bacterial coliforms and faecal coliforms. Water treatment before use in addition to, education on proper water storage methods by community health providers should be emphasized.
Keywords: Borehole water; water contamination; diarrhea; E. coli; faecal coliforms; sanitation